Appendicular dedifferentiated chondrosarcoma: A management and survival study from the SEER database - Marcos R. Gonzalez; Mayte Bryce-Alberti; Arianna Portmann-Baracco; Maria L. Inchaustegui; Samy Castillo-Flores; Juan Pretell-Mazzini (Journal of Bone Oncology, 2022)
Introduction: Dedifferentiated chondrosarcoma (DDC) is an aggressive osseous neoplasm with a dismal prognosis. Treatment commonly involves limb-salvage surgery or amputation. In patients with appendicular DDC, we sought to describe demographic, clinical and treatment characteristics (1), analyze risk factors for metastasis (2) and overall death (3), and assess survival rates by treatment (4). Materials and methods: Two-hundred-and-five patients from the SEER Database were included in our analysis. Demographic, clinical and treatment variables were analyzed. Multivariate regression was performed to identify risk factors. Survival analysis was performed using the Kaplan-Meier method. Results: Fifty-one (24.9 %) of the patients included presented metastasis at diagnosis. The most common locations were the lungs, other sites, and bone. Surgery to the primary site was more common in patients without metastasis (94.2 %) than those with (78.2 %); limb-salvage procedures were more common than amputations. Tumors >8 cm (T2) and those discontinuous (T3) were more likely to present metastasis at diagnosis (OR = 2.54, p = 0.043 and OR = 7.4, p = 0.008, respectively). Female gender was found to be a protective factor for overall death on crude analysis (OR = 0.33, p = 0.019). Metastases to sites other than the lungs (M1b) had the highest risk of overall death (OR = 49, p = 0.01). Combination of surgery and chemotherapy showed a trend towards higher overall survival in non-metastatic patients (p = 0.1069 and p = 0.1703). Conclusions: Appendicular DDC displays a high metastatic rate and low survival rates. The most common procedure is a limb-salvage surgery. Tumor size increases the risk of presenting metastases at diagnosis and female gender is a protective factor against death.